MODEL PEMASARAN BUSINESS-TO-BUSINESS DAN JARINGAN NILAI PRODUK AGROINDUSTRI OLAHAN TEBU MOLASSES - Utami, Hesty Nurul; Hasanah, Gelda Amalia (Economic Faculty, Attahiriyah Islamic University, 2017)
The study objectives were to discover the differences between marketing relationships in companies performing marketing transactional and relational marketing for molasses product trading companies, as well as elaborating the value network conducted by molasses marketer. The data was obtained from the interview with the stakeholders who conduct relationship marketing with molasses trading company and its business partners in Indonesia. The analysis utilized Mann-Whitney test analysis and value network with holo-mapping. The results revealed that there were some differences between companies performing marketing transactional and companies performing marketing relational in terms of power distance variables, social orientation, and uncertainty avoidance. Meanwhile, there was no difference found in masculinity-femininity factor. Value network illustration by looking at the value exchanged among each stakeholder on molasses business from products and services that generate revenues. Keywords: relational marketing, performing marketing